Semantic Web Business Models - Cifliganec, Borce; Trajanov, Dimitar (Institute of Informatics, Faculty of Natural Sciences and Mathematics, Ss. Cyril and Methodius University in Skopje, Macedonia, 2011)
With the emergence of the Semantic Web, that represents an extension of the existing WWW, many opportunities and different ways to use the Internet were created. From the idea to date has spent quite a while and there’s still no appropriate business model that will attract the attention of companies to begin more intensive use of Semantic Web. The semantic web information is a machine understandable format, so the semantic agent who is used by the customer gives pure and relevant information, without any other supporting information that basically is necessary for the classic business model. The need of appropriate business model is more than necessary at a moment when many opportunities for business are open and new rules of operation of e-commerce are introduced. This paper explores new opportunities and exploits the benefits of using semantic web technologies to develop improved and better business models. New business models, on the other hand, will increase business success and profit and will allow faster and easier accomplishment of the final goals. This will empower business capabilities, directly and indirectly, and will lead to positive changes in e-commerce: transparency will increase to satisfactory level, small and medium enterprises will have greater chance for success, access to the consumers will be more direct and increased and they have maximum chance to be found if the offered product fits the needs of customer etc. This paper also presents to entrepreneurs and accomplished business executives new features and functionalities of applications that use semantic web.